SEISMIC ACTIVITY AT KORYAKSKI VOLCANO IN 1994: HYBRID SEISMIC EVENTS AND THEIR IMPLICATIONS FOR FORECASTING VOLCANIC ACTIVITY - Gordeev E.I.; Senyukov S.L. (My University, 2003)
A small swarm of 80 earthquakes was observed beneath Koryakski volcano between March 1 and May 31, 1994. These earthquakes ranged from 0 to 8 km in depth and from −2.0 to 1.5 in magnitude (ML). The swarm under Koryakski volcano was primarily of volcano–tectonic character although a special type of event has been identified with a small amplitude signal preceding the P-wave onset. These precursory signals had varying durations ranging between a few seconds and a few tens of seconds. The source of the signal invariably coincided with the hypocenter of the subsequent earthquake. The origin of these signals may be conjectured to be magma emplacement into weakened zones, which generated a rupture giving rise to a normal tectonic earthquake. The existence of this kind of signals may indicate magmatic activity under the volcano and provide a method for estimating futher development of volcanic activity.